Airship-assisted space launch. - Guenov, Marin D.; Peyron, Vincent (Cranfield University, 2004)
Introduction Being lighter-than-air, airships do not seem to be an obvious platform choice for dropping of heavy objects. We have challenged the idea and this paper presents the summary of a speculative concept which utilises airships as a reusable first stage of a space launch system. The inspiration behind the concept was that if not much cheaper, the airship-assisted space launch will be environmentally friendlier- an argument which is likely to become even more important with time. During the development of the concept we have used as a base for comparison the Orbital Sciences Corp. Pegasus XL concept, which is currently the single operational aircraft-based space launch system. Alongside the challenges of estimating weight and cost of the very large airship required (approximately 728,000 m 3 ), the work presented in this paper concentrates mainly on the process of releasing the space launch vehicle from the airship.